ANALISIS USABILITY LAYANAN BCA MOBILE BANKING BERDASARKAN PERSEPSI PENGGUNA MENGGUNAKAN HEURISTIC EVALUATION - Aviarini Indrati; Bayu Saputra (Asosiasi Dosen Muda Indonesia, 2023)
BCA is the biggest private bank in Indonesia, which is the choice for the public and has an important role in the Indonesian economy. One of the major services is BCA Mobile Banking. BCA also wants the growth of digital services based on the user experience of its customers who feel comfortable, safe and loyal. The purpose of this research is to analyze the interface design and usability of BCA Mobile Banking services using the Heuristic Evaluation method and to analyze the influence of sex, age and duration of user experience. The research method consists of 5 steps, develop a research model and compile the instrument, test the validity and reliability of the instrument, collect the data, process the data and analyze the data. The results of this research are that users have a high level of satisfaction with BCA m-banking services, the level of satisfaction is influenced by sex, age and duration of user experience in service. BCA Mobile Banking has implemented interface design and usability.